Narrators, narratees, and narratives in ancient Greek literature - Jong, Irene J. F. de.; Nünlist, Rene.; Bowie, Angus M. (Mnemosyne, Supplements, 2004)
This is the first in a series of volumes which together will provide an entirely new history of ancient Greek (narrative) literature. Its organization is formal rather than biographical. It traces the history of central narrative devices, such as the narrator and his narratees, time, focalization, characterization, description, speech, and plot. It offers not only analyses of the handling of such a device by individual authors, but also a larger historical perspective on the manner in which it changes over time and is put to different uses by different authors in different genres. The first volume lays the foundation for all volumes to come, discussing the definition and boundaries of narrative, and the roles of its producer, the narrator, and recipient, the narratees.